Basic auditory processing is related to familial risk, not to reading fluency: An ERP study. (February 2015) - Hakvoort, Britt; van der Leij, Aryan; Maurits, Natasha; Maassen, Ben; van Zuijen, Titia L.
Abstract: Less proficient basic auditory processing has been previously connected to dyslexia. However, it is unclear whether a low proficiency level is a correlate of having a familial risk for reading problems, or whether it causes dyslexia. In this study, children's processing of amplitude rise time (ART), intensity and frequency differences was measured with event-related potentials (ERPs). ERP components of interest are components reflective of auditory change detection; the mismatch negativity (MMN) and late discriminative negativity (LDN). All groups had an MMN to changes in ART and frequency, but not to intensity. Our results indicate that fluent readers at risk for dyslexia, poor readers at risk for dyslexia and fluent reading controls have an LDN to changes in ART and frequency, though the scalp activation of frequency processing was different for familial risk children. On intensity, only controls showed an LDN. Contrary to previous findings, our results suggest that neither ART nor frequency processing is related to reading fluency. Furthermore, our results imply that diminished sensitivity to changes in intensity and differential lateralization of frequency processing should be regarded as correlates of being at familial risk for dyslexia, that do not directly relate to reading fluency.